Skills, parental background, and changes in educational institutions - Jani Erola; Valeria Breuker (INVEST Research Flagship, 2022)
In this study, we test how educational expansion, prolonging education, and educational reforms have contributed to the improvement of skills in developed societies in recent decades. We expect that the growing openness of the educational system is associated with higher gains in cognitive skills, but that there are several multiplicative and compensatory processes related to both family background and the educational institutions involved that can alter these trends, depending on family background. We test the assumptions with the first wave (2013) of the Program for the International Assessment of Adult Competencies (PIAAC) data, linked with birth-cohort-specific, macro-level information on the changes in educational institutions in each country. The results suggest that the growing proportion of those with a tertiary education as well as the prolonging of education are associated with the improvement of skills, partially because these changes are also associated with the increased effectiveness of education in the improvement of skills. However, the growing number of reforms in general tend to harm the skill development especially of those with poorly educated parents, even if the reforms were intended to remove educational dead-ends.